A hybrid model for human-factor analysis of engine-room fires on ships: HFACS-PV&FFTA. (1st December 2020) - Sarıalioğlu, Songül; Uğurlu, Özkan; Aydın, Muhammet; Vardar, Burak; Wang, Jin
Abstract: In this study, an analysis of fire-explosion accidents in ship engine rooms was conducted. For analysis, a hybrid method including the Human Factors Analysis and Classification System (HFACS) and fuzzy fault tree analysis (FFTA) was used. Using the HFACS method, the factors in the formation of engine-room fires were classified according to a hierarchical structure. The possible accident scenarios and probabilities were calculated using the FFTA method. In this study, it was observed that fire-explosion accidents were concentrated in ships over 20 years old and that mechanical fatigue affected accident formation. In particular, when the increased hot surfaces due to the operation of a ship's engines while it is in motion are combined with oil/fuel leakage, fire-related accidents become inevitable. Failure to provide proper insulation also triggers the occurrence of accidents. It has been observed that some of such accidents occur because the materials used in maintenance and repair work are not original to the ship. During this study, the causes of accidents were examined to prevent fire-related accidents from occurring in engine rooms, and suggestions were made to prevent similar accidents from happening in the future. Highlights: The HFACS-PV structure used in this study presents information about the human errors that cause engine room fires. The most likely accident scenarios and probabilities were calculated by using the FFTA method in this study. This study suggests a hybrid model for analysis of ship engine room fires.